Developing Pre-service Teachers Conceptualization of STEM and STEM Pedagogical Practices - Berisha, Fatlume; Vula, Eda (Frontiers in Education, 2021)
Science, Technology, Engineering, and Mathematics (STEM) integrated curricular approach has become the leading education reform worldwide. This paper presents a STEM integrated collaborative activity to enhance STEM knowledge among pre-service mathematics and chemistry teachers. Well-structured and planned on-site workshops on STEM activities were delivered to pre-service teachers while growing mathematics and science content knowledge and pedagogical practices. The qualitative content analysis research methodology was used to identify relevant topics related to post reflective questions regarding pre-service teacher perspectives on the experience gained through collaborative practices at the STEM workshop. The results show that the workshop had a positive effect on pre-service teachers' conceptualization of STEM - through collaborative, participatory practices, an effective learning environment while bringing attention to teacher professional development and education policymakers. Key elements of this study approach included: (1) collaboration between university professors to teach and incorporate STEM in higher education, (2) unique partnership among mathematical and chemistry pre-service teachers, (3) professional development that is devoted and adopted into a study course.